In vitro validation of endovascular Doppler-derived flow rates in models of the cerebral circulation. (9th October 2015) - McGah, P M; Nerva, J D; Morton, R P; Barbour, M C; Levitt, M R; Mourad, P D; Kim, L J; Aliseda, A
Abstract: This study presents validation of endovascular Doppler velocimetry-based volumetric flow rate measurements conducted in a pulsatile flow loop simulating conditions in both the internal carotid and basilar artery. In vitro models of cerebral vessels, each containing an aneurysm, were fabricated from patient anatomies extracted from 3D rotational angiography. Flow velocity measurements were collected with three different experimental techniques: an endovascular Doppler wire, Particle Image Velocimetry, and a time-resolved ultrasonic flow meter. Womersley's theory of pulsatile flow in a cylindrical vessel was used to compute time-resolved volumetric flow rates from the endovascular Doppler velocity. The volumetric flow rates computed from the Doppler measurements were compared to those from the Particle Image Velocimetry profile measurements, and the direct measurements from the ultrasonic flow meter. The study establishes confidence intervals for any systematic or random errors associated with the wire-derived flow rates as benchmarked to the other two modalities. There is an approximately 10% random error in the Doppler-derived peak and time-averaged flow rates. There is a measurable uniform bias, about 15% too low, in the time-averaged Doppler-derived flow rates. There is also a small proportional bias in the peak systolic Doppler-derived flow rates. Potential sources of error are also discussed.